Acute oral toxicity assessment of ethanolic extracts of Antidesma bunius (L.) Spreng fruits in mice - Maria Nilda M. Muñoz; Urdujah G. Alvarado; Jerica Isabel L. Reyes; Kozo Watanabe (Toxicology Reports, 2021)
The aim of the study is to assess the acute oral toxicity of ethanolic extracts of Antidesma bunius (L.) Spreng [Bignay] in ICR mice in accordance to OECD guideline 423. Single doses of Bignay fruit extracts ranging from 500 mg/kg to 2000 mg/kg, as well as a vehicle control, were given orally and monitored for 14 days. We observed that there is no mortality or adverse effects after treatment of mice indicating that Bignay extracts are safe for use in laboratory animals. Behavioral, respiratory, and neurologic changes, as well as changes in body weight, food and water consumption, did not occur during the experimental period. Hematological- (total-red and -white blood cells) and biochemical-profile analysis (alanine transaminase, blood urea nitrogen, and creatinine) remained within normal concentrations in treated mice regardless of sex. The morphology of visceral organs in all treated mice was typical in appearance when stained with H&E. It is assumed that the LD50 is greater than 2000 mg/kg and there is no mortality at the maximum dose used (2000 mg/kg). We have also determined the active components of dried Bignay by headspace GC–MS and by phytochemical analysis of ethanolic Bignay extracts. We have identified 16 compounds by GC–MS and 10 secondary metabolites. In this study, the assessment of extracted Antidesma bunius (L.) Spreng fruits [Bignay] on the value of safety measures in mice is described.